Circular bioeconomy for sustainable resource management and livelihood improvement in Ethiopia - Bodach, Susanne; Alegbeleye, Oluwadara; Taron, Avinandan; Hagos, Fitsum (2024)
Ethiopia faces a growing challenge of balancing natural resource utilisation with long-term sustainability. Its linear economic model leads to unsustainable waste generation from agriculture, urban populations, and the industry sectors. This paper explores the potential of a circular bioeconomy (CBE) as a solution. By promoting closed-loop systems that minimise waste and maximise resource use, CBE offers a pathway for Ethiopia to achieve sustainable resource management, economic growth, and better livelihood opportunities. CBE business models create valuable products such as organic fertiliser, biochar, bioenergy, and alternative proteins. CBE practices provide new income opportunities for farmers and urban dwellers and reduce the country’s reliance on virgin resources, chemical fertiliser, and non-renewable energy while addressing environmental pollution and soil depletion.